P227 Remote monitoring of patients with RA: a user-centred design approach. (20th April 2020) - Martin, Melanie J; Ng, Nora; Blackler, Laura; Garrood, Toby
Abstract: Background: Patients with rheumatoid arthritis are generally seen at arbitrary intervals in secondary care. Patients with active disease may not always be seen at the most appropriate time and those with low disease activity may be seen more frequently than necessary. The NHS Long Term Plan expects outpatient appointments to be reduced by up to a third, with digital transformation a key enabler. The remote capture of patient-reported outcome measures (PROMs) has the potential to facilitate more flexible and responsive outpatient services. Methods: This project aimed to design a digital remote monitoring platform to test the hypothesis that PROMs can be used to proactively monitor and trigger consultations when patients need them most. The Rheumatoid Arthritis Impact of Disease (RAID) questionnaire, a validated multidimensional PROM, was used. Waiting room testing with patients informed the design of an acceptable mobile device format of the RAID. Recruitment criteria and acceptable cut-offs for defining flare were agreed by the rheumatology multidisciplinary team. Patients in low disease activity or remission (DAS <3.2) were invited to the service via SMS. All patients were informed regarding the governance of handling patient data and an opt-out option was offered. Patients were sent an automated monthly SMS with a PROM link and weekly reminder SMS if required. They also had the option to send in SMS messages at other times or add free text comments. Patients submitting a RAID score of ≥ 4 received a SMS with a link to the rheumatology advice service advising a remote consultation. The SMS-based service went live in January 2019 and all incoming communication was monitored on a daily basis. Results: 104 RA patients are currently using the remote monitoring service with 10.3% (13/117) opting-out. 847 monthly PROMs have been sent via SMS. The PROM completion rate has been 68.9% (range 59.0-85.1%). 120 RAID (21.8%) scored 2-≤4 indicating low disease activity and 136 RAID (24.7%) ≤ 2 indicating disease remission. 480 SMS have been sent manually to patients who have engaged in two-way communication or returned a RAID score ≥4. 44 telephone advice appointments were triggered through the remote monitoring service by patients in disease flare. 80% (35/44) of remote consultation were considered to have to have averted a face to face consultation with the remaining 20% providing advice alone. Interviews have been conducted with PROM 'non-completers' to learn and inform further service design. Conclusion: This project has demonstrated how a user-centred design approach to utilising technology can support access to rheumatology care when patients need it most, such as disease flare. The identification of patients self-reporting low disease activity using multidimensional PROMs may enable more efficient utilisation of clinical capacity through patient-initiated appointment deferment and lead to improved patient-centred care. Disclosures: M.J. Martin: Honoraria; Novartis, Abbvie. Grants/research support; National Ankylosing Spondylitis Society. N. Ng None. L. Blackler None. T. Garrood None.